Inmunolocalizacion de CD31 como marcador de vasos sanguíneos placentarios, su aplicación en estudios histomorfométricos - Fiorimanti, Mariana Rita (2018)
For study of placental angiogenesis in productive interest species, it is necessary to have a specific marker of different caliber blood vessels, which allows to apply vascular histomorphometryc. The objective was to develop the immuno histochemical technique for CD31 as marker of blood vessels in placentas of swines at the early gestations, intermediates gestations and term gestations,for histomorphometric studies. The histological sections of 4 μm were stained with differential stains and the other processed by indirect immunohistochemistry for the determination of the endothelial cell marker protein, CD31. The histomorphometric analysis revealed a significant increase in the number of blood vessels in the placenta from day 30 to 60 of gestation and a decrease in the vascular area in intermediates gestations (p=0.05). The immunolocalization of CD31allowed us to delimit with precision smaller vascular areas. We consider that the marking placental micro vasculature through the immuno localization of CD31 is an effective tool for the application of histomorphometric studies.